Identification of Homogentisate Dioxygenase as a Target for Vitamin E Biofortification in Oilseeds . Issue 3 (22nd September 2016) - Stacey, Minviluz G.; Cahoon, Rebecca E.; Nguyen, Hanh T.; Cui, Yaya; Sato, Shirley; Nguyen, Cuong T.; Phoka, Nongnat; Clark, Kerry M.; Liang, Yan; Forrester, Joe; Batek, Josef; Do, Phat Tien; et al.
Abstract : Reduced homogentisate catabolism due to homogentisate dioxygenase deficiency offers a novel strategy to increase vitamin E production and herbicide tolerance in plants. Abstract: Soybean ( Glycine max ) is a major plant source of protein and oil and produces important secondary metabolites beneficial for human health. As a tool for gene function discovery and improvement of this important crop, a mutant population was generated using fast neutron irradiation. Visual screening of mutagenized seeds identified a mutant line, designated MO12, which produced brown seeds as opposed to the yellow seeds produced by the unmodified Williams 82 parental cultivar. Using forward genetic methods combined with comparative genome hybridization analysis, we were able to establish that deletion of the GmHGO1 gene is the genetic basis of the brown seeded phenotype exhibited by the MO12 mutant line. GmHGO1 encodes a homogentisate dioxygenase (HGO), which catalyzes the committed enzymatic step in homogentisate catabolism. This report describes to our knowledge the first functional characterization of a plant HGO gene, defects of which are linked to the human genetic disease alkaptonuria. We show that reduced homogentisate catabolism in a soybean HGO mutant is an effective strategy for enhancing the production of lipid-soluble antioxidants such as vitamin E, as well as tolerance to herbicides that target pathways associated with homogentisate metabolism. Furthermore, this work demonstrates the utility of fast neutron mutagenesis in identifying novel genes that contribute to soybean agronomic traits.